Islamic Sustainable Finance and MSME Development in Indonesia: Evidence from Bank Syariah Indonesia - Ahmad Afif; Ade Wirman Syafei; Siti Hamidah Binti Marwan (Journal of Islamic Economics Perspectives, 2025)
This paper investigates the critical yet under-explored impact of Islamic sustainable finance reporting on the inclusiveness and distribution of financing to Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Despite a robust regulatory framework, a significant financing gap persists for MSMEs, raising questions about the efficacy of current sustainable finance initiatives beyond mere reporting. Utilising a quantitative approach, this research analyses data from Bank Syariah Indonesia (BSI), the nation's largest Islamic bank, from 2021 to 2024. Simple regression analysis was employed to examine the relationship between key performance metrics. The results reveal a stark dichotomy: a strong, perfect positive relationship (coefficient = 1.000) was found for Success Rate (SR), indicating that sustainable finance principles, when implemented, are highly effective in driving genuine inclusive outcomes for MSMEs. Conversely, the analysis of the Financing to Deposit Ratio (FDR) showed a non-significant coefficient (0.038), a negative R-squared (-0.071), and a high p-value (0.99), indicating that the current framework fails to systematically differentiate true inclusiveness from consistent error, suggesting potential "SDG-washing". The study concludes that while Islamic sustainable finance provides a potent framework for success, its current implementation lacks the sophisticated risk assessment and auditing mechanisms needed to ensure authentic and scalable financing distribution. The findings urge policymakers and financial institutions to enhance the discriminative power of sustainable finance metrics, moving beyond reporting to develop granular tools that prioritise and authentically support Indonesia's vital MSME sector.